The soft power of the Korean wave Parasite, BTS and drama - Kim, Youna (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2022)
"Focusing on the recent phenomenon of Korean popular culture, Parasite, BTS and drama at an unprecedented historic moment, this book explores the multifaceted meaning of the Korean Wave at micro and macro levels and the process of media production, representation, circulation and consumption in a global context as a distinctive and complex form of soft power. It considers the Korean Wave in the digital social media age and addresses the social, cultural and political implications in their complexity and paradox within the contexts of global inequalities and uneven power structures. The book explores the global success of the Korean Wave as a pronounced example of the crossover of culture, economy and politics and the emerging consequences of the postcolonial, alternative and competing power. The globalization of media content from once subalternized or peripheral nations such as Korea is a facet of de-centralizing multiplicity of global cultural flows today, emerging as subversive soft power resources that challenge the Western hegemony of dominant ideas, values and ways of life."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mass media -- Korea (South); Mass media -- Social aspects; Civilization, Modern -- Korean influences; Korea (South) -- Popular culture